The Effectiveness of IMCI (Integrated Management of Childhood Illness) Mini Training in Improving Health Workers’ Skills in Primary Health Centers in Bantul - RR Anugrah Wiendyasari; Hari Kusnanto; Tunjung Wibowo (Faculty of Medicine, Public Health, and Nursing, 2018)
ABSTRACTBackground: At the Community and Primary Health Care Center in Bantul, the number of paramedics receiving Integrated Management of Childhood Illness (IMCI) training is very limited and not evenly distributed. With the low number of IMCI trained officers, this affects the skill of the officers in conducting the IMCI. Fewer skills affect the handling of sick children including the recognition of general danger signs, classification, designing appropriate action, as well as providing treatment and counseling.Objective: This study aimed to know the effectiveness of IMCI Mini Training intervention to improve health workers’ skills in handling sick children with IMCI.Methods: This research was a quasi-experimental study with a non-equivalent pre-post control group design. The sample of this study was a group of health workers who implement IMCI in daily work at 20 Community and Primary Health Care Centers in Bantul. Data were collected by observing 20 health workers in the control group and 20 health workers in IMCI treatment group before and after receiving IMCI Mini Training. Data results were analyzed using univariate, bivariate and multivariate statistical tests.Results: Using t-test analysis the mean value of health worker’s pretest and posttest skill scores in implementing IMCI in control group showed no significant difference (p=0.857) while in the treatment group, the mean value of pretest and posttest score showed a significant difference (p=0.000). In the treatment group, the improvement of sign recognition skills was significant (p=0.000) compared with the classification (p=0.148), treatment (p=0.009), communication and counseling (p=0.005). Multivariate analysis of linear regression showed that IMCI Mini Training was significant in improving the skill of health workers (p=0.000) compared with variables: age (p=0.970), duty (p=0.425), IMCI training history (p=0.686), category of Community and Primary Health Care Center (p=0.409) and education (p= 0.474). IMCI Mini Training improved significantly the sign recognition skills (p=0.000), classification (p=0.001) as well as communication and counseling (p=0.011) but was not significant in treatment skill (p=0.093). IMCI Mini Training can be done in a shorter time and more interactive method by using ICATT.Conclusion: This study showed that IMCI Mini Training increased health workers’ skills in IMCI implementation with the advantages of shorter course time, lower cost, and more interactive methods. The IMCI skills were enhanced by the provision of IMCI Mini Training which includes skills in the recognition of common signs, classifications as well as providing appropriate communication and counseling.